The effect of altered pH on push-out bond strength of biodentin, glass ionomer cement, mineral trioxide aggregate and theracal - Makkar Sameer; Vashisht Ruchi; Kalsi Anita; Gupta Pranav (Serbian Medical Society - Dental Section, Belgrade, 2015)
Throughout the history of dentistry, a wide variety of materials such as gold-foil, silver posts, amalgam, zinc oxide eugenol, glass ionomer cements, mineral trioxide aggregate have been used as retrograde fillings. Altered pH in periapical lesions can affect push-out bond strength of these materials. The aim of this study was to evaluate the effect of altered pH on push-out bond strength of Biodentin, Glass ionomer cement (GIC), Mineral trioxide aggregate (MTA) and Theracal. Material and Methods Forty-eight dentin slices of extracted single-rooted human teeth were sectioned and their canal portion instrumented to achieve a diameter of 1.4 mm. The specimens were then assigned into the four groups (one group for each material) with 12 samples in each group. All groups were further divided into 3 subgroups (with 4 specimens in each subgroup): acidic (butyric acid buffered at pH 6.4), neutral (phosphate buffer saline solution at pH 7.4) and alkaline (buffered potassium hydroxide at pH 8.4). Samples were incubated for 4 days at 37°C in acidic, neutral or alkaline medium. Push-out bond strength was measured using a Universal Testing Machine. The slices were examined under a stereomicroscope to determine the nature of bond failure. Results GIC showed the highest bond strength (33.33MPa) in neutral and acidic medium (26.75MPa) compared to other materials. Biodentin showed the best result in alkaline medium. Conclusion Altered pH level affected push-out bond strength of root end materials. GIC demonstrated good push-out bond strength that increased with decrease of pH whereas newer materials Biodentin and Theracal showed satisfying results in altered pH.